Is Turkey still an emigration country? - Secil Pacaci Elitok; Thomas Straubhaar (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
Located at the geographical intersection between East and West, with both Mediterranean and Black Sea coasts, Turkey was always a country with large movements of people. There were several waves of forced (ethnic) movement of people as a consequence of the collapse of the Ottoman Empire and the following nation-building process in the Turkish neighborhood. In the post-Second world war period, Turkey became a country of emigration. In 1961 a bilateral agreement on labor recruitment between Turkey and Germany had been signed. In the following years, similar bilateral agreements were reached with a couple of other European countries (Austria, Belgium, France, the Netherland and Sweden). Nowadays, things have changed. Turkey is still a country of emigration. But it has also become a country of immigration and transit. And therefore, it faces similar challenges of migration and integration that are characteristic for areas with strong cross-cultural movements of people. In this paper, we concentrate on the emigration flows.
Keywords: 330